Population Dynamics of Bagrus bayad macropterus from Dadin– Kowa Reservoir, Nigeria: Population Dynamics of Bagrus bayad macropterus from Dadin– Kowa Reservoir, Nigeria - Nazeef S; Ramatu M. T. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
The population dynamic parameters of Bagrus bayad macropterus from Dadin-Kowa reservoir were studied. Population dynamic parameters such as growth, mortality and recruitment patterns were analyzed using length frequency data over 12-month period employing FiSAT II software. Findings revealed that K = 0.94-yr., L∞ = 75.75 cm and Tmax = 3.73 years. Mortality indices revealed that the fish is slightly above exploitation threshold (F > Eopt ≤ 0.5). However; the major source of population decay is associated with fishing factors (F = 2.56-yr.). Bimodal recruitment pulses were observed with Lm = 50.5 cm, Lc/ L∞ = 0.15. Restocking program is suitable to ensure its continuous existence as it seems to have low population, and experiencing recruitment overfishing.